ANALYSIS AND ASSESSMENT OF THE IMPACT OF AGRICULTURAL ACTIVITIES ON LAND DEGRADATION: (on the example of the Lori Region) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
In the article influence of agricultural activities on land degradation with the help of Lori Marz example were assesed and analysed. It gives the opportunity to detect and manage negative anthropogenic interference, which will minimize land degradation in the region.
Keywords: crop rotation; irrigation regime; migration of elements; overgrazing; land approval; landscape over freight